CASES OF MOBILE THROMBUS IN THE CORONARY ARTERIES - S. A. Prozorov; S. R. Giliarevsky (Неотложная медицинская помощь)
ABSTRACT. Five cases of mobile thrombus identified in the coronary arteries by coronarography have been described. Controlled coronarography performed after therapy completion demonstrated thrombus resolution.